(untitled) (Academia Journal of Medicine, 2021)
Background: Hypocalcemia has been demonstrated in various tropical diseases, such as leptospirosis, malaria, including dengue. Calcium is believed to play a major role in the immune response in dengue. It has been proposed that the derangements of Calcium levels in the infected myocardial cells may play a major role in development of myocarditis. This study aims to correlate the serum calcium levels with severity of dengue and bradycardia. Subjects and Methods: This study was conducted on 100 dengue positive patients, above the age of 18 years, presenting to BMCRI, after obtaining informed consent. Dengue test kit was used for diagnosis which is based on rapid solid phase immunochromatographic test. Physical examination and routine investigations along with serum calcium levels were done and assessed. Radiological imaging was done wherever necessary. They were grouped into one of the three WHO categories based on severity and were correlated with serum calcium levels. Results: Out of 100 patients 65 patients had uncomplicated dengue fever while 30 had dengue fever with warning symptoms and 5 has severe dengue/ dengue shock syndrome. Chi-square test showed statistical significant association between severity of dengue and hypocalcemia. (χ2= 94.08; p=0.00). Statistical analysis revealed significant association between serum calcium levels and pulse rate (χ2= 16.01; p=0.00). Conclusion: Our study and several other studies showed that the presence of hypocalcemia correlates with the severity of Dengue illness and could be considered as one of the predictors of poor outcome. However, further studies are required in these lines that are aimed at understanding if the presence of hypocalcemia can be utilized as a prognostic indicator in dengue infection. The potential role of calcium as a treatment option, to modulate the immune system, in patients with dengue is to be explored.